Efficacy and safety of EMA401 in peripheral neuropathic pain: results of 2 randomised, double-blind, phase 2 studies in patients with postherpetic neuralgia and painful diabetic neuropathy. Issue 10 (October 2021) - Rice, Andrew S.C.; Dworkin, Robert H.; Finnerup, Nanna B.; Attal, Nadine; Anand, Praveen; Freeman, Roy; Piaia, Alessandro; Callegari, Francesca; Doerr, Christie; Mondal, Subhayan; Narayanan, Nisha; Ecochard, Laurent; et al.
Abstract : Abstract: The analgesic efficacy and safety of 2 phase 2b studies of EMA401 (a highly selective angiotensin II type 2 receptor antagonist) in patients with postherpetic neuralgia (EMPHENE) and painful diabetic neuropathy (EMPADINE) were reported. These were multicentre, randomised, double-blind treatment studies conducted in participants with postherpetic neuralgia or type I/II diabetes mellitus with painful distal symmetrical sensorimotor neuropathy. Participants were randomised 1:1:1 to either placebo, EMA401 25 mg, or 100 mg twice daily (b.i.d) in the EMPHENE and 1:1 to placebo or EMA401 100 mg b.i.d. in the EMPADINE. The primary outcome for both the studies was change in weekly mean of the 24-hour average pain score, using a numeric rating scale from baseline to week 12. Both the studies were prematurely terminated due to preclinical hepatotoxicity on long-term dosing, although not observed in these studies. Out of the planned participants, a total of 129/360 (EMPHENE) and 137/400 (EMPADINE) participants were enrolled. The least square mean reduction in numeric rating scale pain score was numerically in favour of EMA401 100 mg arm in both EMPHENE (treatment difference: −0.5 [95% confidence interval: −1.6 to 0.6; P value: 0.35]) and EMPADINE (treatment difference: −0.6 [95% confidence interval: −1.4 to 0.1; P value: 0.10]) at the end of week 12. However, as the studies were terminated prematurely, no firm conclusion could be drawn but the consistent clinical improvement in pain intensity reduction across these 2 studies in 2 different populations is worth noting. Abstract : Supplemental Digital Content is Available in the Text. EMPHENE and EMPADINE studies, although prematurely terminated, demonstrated that EMA401 was well tolerated and showed numerically greater improvement in pain intensity vs placebo in patients with postherpetic neuralgia and painful diabetic neuropathy.